Trust e affidamenti fiduciari nel confronto tra "modello" sammarinese e italiano - Di Bona, Laura (Cultura giuridica e diritto vivente, 2018)
[Trust and entrustments in the comparison between the “model” of San Marino and Italian] The essay shows that the San Marino system is endowed with a completeness and a capacity for adaptation to the becoming of a reality far greater than that of the neighboring Italian legal system, and this is also demonstrated in the discipline of trust and fiduciary assignments. In fact, in the Italian legal system, the principles of patrimonial responsibility, indivisibility of the patrimony, typical of the real rights, in addition to the prohibition of the commission pact and the successor pacts, have made the insertion of such institutions more difficult. On the other hand, in the Sammarinese system the architecture of the sources and the extraordinary role played by the common law facilitate a harmonious and natural regulation of the new operations emerging from the social and economic reality. Key Words: Trust, responsabilità patrimoniale, diritto comune